Implementation of Sandhi Viccheda for Sanskrit Words/Sentences/Paragraphs - Patil, Bhagyashree; Patil, Manoj (International Journal of Computer Sciences and Engineering, 2018)
Sandhi is a technique in which joining of two or more words happens. Sandhi viccheda means splitting of word or sentences into its constituents. Languages like Hindi, Urdu, Marathi, Kannada, and Malayalam are used to implement the sandhi viccheda concept. Sanskrit is a language in which rules are used to form a word. These rules play an important role in sandhi viccheda process. So, to split the word or sentence rules are used in the system. As everyone knows BHAGWAT GEETA is a religious book which contains more complex words, sentences, which user can’t understand. The proposed system uses those words, sentences from BHAGWAT GEETA for splitting purpose. For this, rules of sandhi viccheda like (vowels, consonant, and visarga) are used. The representation of the splits is shown using the directed acyclic graph to get a number of possible outputs